Hubungan Pengetahuan Dan Personal Hygiene Ibu Dengan Kejadian Diare Pada Balita Di Kelurahan Pagar Dewa Kota Bengkulu - Agus Widada; Depriyani; Yusmidiarti (Jurnal Sanitasi Profesional Indonesia, 2026)
Diarrhea is the highest cause of death for children under the age of 5 in the world, which is around 760,000 cases every year. Data from the Ministry of Health of the Republic of Indonesia in 2018 This study aims to determine the relationship between maternal Personal Hygiene behavior with the incidence of diarrhea in the Pagar Dewa sub-district, Bengkulu city in 2022. This study is an analytic with a cross sectional approach with a sample of the community in the Pagar Dewa sub-district, Bengkulu City. The analysis used is chi-square, the results of the study are the knowledge category of a total of 92 known as many as 30 respondents with good knowledge (32.6%), 52 respondents with good knowledge (56.5%), and 10 respondents with poor knowledge (10.9%), Personal category Mother's Hygiene as many as 92 respondents, 69 respondents (75.0%) and the category of incidence of diarrhea with a frequency distribution, 92 respondents, 26 respondents (28.3%) experienced diarrhea and 66 respondents (71.7%) did not experience diarrhea. Meanwhile, for the relationship between Knowledge and Mother's Personal Hygiene with Diarrhea in Toddlers in Pagar Dewa Village, Bengkulu City, the results of the chi-square statistic test, for knowledge, p-value = 0.000 (there is a relationship), for Mother's Personal Hygiene, p-value = 0.061( no connection).